Distinct Functions of the Atypical Terminal Hydrophilic Domain of the HKT Transporter in the Liverwort Marchantia polymorpha. (5th April 2022) - Imran, Shahin; Oyama, Masumi; Horie, Rie; Kobayashi, Natsuko I; Costa, Alex; Kumano, Ryosuke; Hirata, Chiho; Tran, Sen Thi Huong; Katsuhara, Maki; Tanoi, Keitaro; Kohchi, Takayuki; Ishizaki, Kimitsune; et al.
Abstract: K + /Na + homeostasis is important for land plants, particularly under salt stress. In this study, the structure and ion transport properties of the high-affinity K + transporter (HKT) of the liverwort Marchantia polymorpha were investigated. Only one HKT gene, Mp HKT1, was identified in the genome of M. polymorpha . Phylogenetic analysis of HKT proteins revealed that non-seed plants possess HKTs grouped into a clade independent of the other two clades including HKTs of angiosperms. A distinct long hydrophilic domain was found in the C-terminus of Mp HKT1 . Complementary DNA (cDNA) of truncated Mp HKT1 ( t- Mp HKT1 ) encoding the MpHKT_Δ596-812 protein was used to examine the functions of the C-terminal domain. Both Mp HKT1 transporters fused with enhanced green fluorescent protein at the N-terminus were localized to the plasma membrane when expressed in rice protoplasts. Two-electrode voltage clamp experiments using Xenopus laevis oocytes indicated that Mp HKT1 mediated the transport of monovalent alkali cations with higher selectivity for Na + and K +, but truncation of the C-terminal domain significantly reduced the transport activity with a decrease in the Na + permeability. Overexpression of Mp HKT1 or t-Mp HKT1 in M. polymorpha conferred accumulation of higher Na + levels and showed higher Na + uptake rates, compared to those of wild-type plants; however, phenotypes with t-Mp HKT1 were consistently weaker than those with Mp HKT1 . Together, these findings suggest that the hydrophilic C-terminal domain plays a unique role in the regulation of transport activity and ion selectivity of Mp HKT1 .